PEMBUANGAN AIR LIMBAH INDUSTRI FARMASI OLEH PT. X BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP: Pharmacy Industry Waste Water Disposal By LLC. X Based On Law Number 32 Of 2009 Concerning Protection and Management Environment - Sagala, Juan Gilbert; Siswanto, Wahyudi (AMICUS CURIAE, 2024)
Industrial developments that continue to grow must be monitored so that they do not pollute the environment which can cause environmental damage which is regulated to be maintained based on Law Number 32 of 2009 (UUPPLH). The author discusses the problem of the suitability of waste disposed of by PT. X with the provisions of UUPPLH and the law enforcement process resulting from the disposal of waste water by PT DKI Jakarta Environment. The data collection method is carried out by analyzing literature using a qualitative approach from which conclusions will then be drawn deductively. After the research was carried out, it was concluded that the waste disposal carried out by PT. Dr. The lifting of sanctions was also appropriate because PT. X has carried out the sanctions given well